Peso de Drude em anéis unidimensionais com potenciais de substituição e atravessados por fluxo magnético - Prado, Fabiano Oliveira (2002)
In the present work the Drude weight is calculated to study the capacity of conduction at finite temperatures in one-dimensional rings with the potencial given by the sequences of different degrees of randomness and threaded by a time independent magnetic flux. In this context, the tight-binding approximation is used to solve the Schrödinger equation,also permitting the potencials, given by substitution sequences, to be implemented in a simple way. We study four situations in which the potencial is given by periodic and random sequence. The transport properties exhibited by the system in each case are to reflect the degree of randomness presented by these potencials, although in a nontrivial manner if one considers a hierarchy of disorder based on the Fourier transform of the sequences. The role played by temperature in the capacity of conduction, as compared with the role played by the potencials, is also described.